Cognitive impairment in patients with acute myocardial infarction: an assessment of the role of arrhythmic factors - Natalya Akimova; Ekaterina E. Kutorova; Larisa E. Konshina; Alexander A. Ryabov; Yury G. Shvarts (Exploration of Medicine)
Aim: A growing body of research suggests that acute myocardial infarction (AMI) may be an independent risk factor for cognitive impairment in patients with cardiovascular disease. The role of premature ventricular contractions (PVCs) or premature atrial contractions (PACs) occurring during the day has not been fully explored in this patient population. The objective of the study was to investigate the clinical and functional relationships between cognitive functions and the severity of daytime premature cardiac contractions, as well as echocardiographic parameters in patients with either old myocardial infarction (OMI) or recent AMI. Methods: The main group consisted of 32 patients who had experienced an AMI no more than seven days prior. The comparison group included 20 patients who had had one myocardial infarction more than one year earlier. All participants underwent a 24-hour Holter monitoring, Doppler echocardiography. Cognitive testing included the Mini-Mental State Examination, Wechsler Subtests 5 and 7, and the Bourdon Test. Statistical methods included multivariate analysis, univariate analysis of variance, canonical correlation analysis, nonparametric correlation analysis, and multivariate analysis was also performed using the generalized normalized log model. Results: In the patients of the main group, the characteristics of mental functions were worse than in the control group. The cognitive test scores were significantly correlated with the presence of akinesia zones in the myocardium, as well as with a higher grade of PVCs and a large number of PVCs during the day in patients with AMI. No significant correlations were found between cognitive test results and echocardiographic findings in the comparison group, a weak correlation was only noted between the number of PACs and cognitive test results. Conclusions: The presence of even non-life-threatening PVCs occurring within 24 hours may be a marker of significant cognitive deficit in the acute period of myocardial infarction.